Leader power of Islamic higher education institutions in improving the performance of human resources management - Jamali Sahrodi; Abdul Karim (Cogent Arts & Humanities)
The job distribution is improving the quality of institutions and products to be produced. This research purposed to analyze the UIN Siber Syeh Nurjati Cirebon Indonesia Institution leaders’ power in improving the performance of human resources management (HRM) through staffing policies. The research problem is that HRM must get serious attention from the institution leader in providing maximum service to the community. The research method used a descriptive-analytic case study, by conducting in-depth interviews with 17 educational staff and lecturers who were affected by the rector’s policy. The findings showed that there was a difference in the officials’ appointment within the institution environment between the initial period and the second period of the Rector leadership. There were some less-positive trends in the officials’ appointment in the institution environment. A brief summary is that the leaders of higher education play a huge role. The top leadership has absolute authority to determine the officials under his leadership. Several recommendations to be made policies that must be bottom-up, management control of top leader authority, conducting need assessment, managerial training, and making improvements to the qualification system. The implication of this research is to restore the function of position and rank consideration board and bottom-up policies in human resource management in these institutions.